STUDENT MOTIVATION TO PARTICIPATE IN THE MARTIAL STUDENT ACTIVITY UNIT: A CASE STUDY OF UKM STUDENT SPORTS FEDERATION (FORSA) UIN JAKARTA - Salwa Fadiah Afif; Mayra Angie Zaneta Tiara Nida; Niswa Ibda Sanatin; Naufal Rifky Pradana; Arif Saefudin (Yayasan Amanah Nur Aman, 2026)
This study aims to analyze the motivation of students participating in martial arts clubs (UKM) under the Student Sports Federation (FORSA) at UIN Syarif Hidayatullah Jakarta. The research employs a descriptive qualitative approach through in-depth interviews with four informants representing various martial arts disciplines. The findings reveal that students’ motivation is predominantly driven by intrinsic factors such as interest, personal satisfaction, and the desire to develop physical and mental abilities. Extrinsic motivations, including social support, peer encouragement, and opportunities for achievement, also reinforce students’ enthusiasm for active participation. Martial arts activities within FORSA offer extensive benefits physically, mentally, and socially—by enhancing fitness, building character, and fostering soft skills such as discipline, leadership, and self-confidence. Overall, FORSA plays a crucial role as a platform for character development and strengthening the identity of resilient, sportsmanlike, and integrity-driven students.